The Role of Transalpine Freight Transport in a Common European Market: Analyses and Empirical Applications - Aura Reggiani; Peter Nijkamp; Simona Bolis (Tinbergen Institute, 1997)
The paper focuses on the Trans Alpine Freight Transport systems in the light of the future integration of single national transport systems into the European transport network. The environmental, social and institutional peculiarities of this 'region' have favoured - in the past - the development of strong nationally-oriented policies, which are largely in contrast with the goals promoted by the European Union. The present analysis aims to highlight opportunities and limits inherent in the implementation of various new network projects, with a particular view on the planned changes of the Alpine transportsystem. In this framework, a concise description of the existing and 'planned' situation will be offered.In addition, some new forecasting analyses for road transport will be offered on the basis of environmentally-based transport scenarios. In particular, given the high dimension of our data-base on European transport flows, two different approaches will be compared, viz. the logit model and the neural network model. Logit models are well-known in the literature; however, applications of logitanalysis to large samples are more rare. Neural networks are nowadays receiving a considerable attention as a new approach that is able to capture major patterns of spatial flows, on the basis of fuzzy and incomplete information. The tentative results of both approaches in this context may then be usedas a benchmark for judging the results of other transport flow models and offer also a more 'flexible' range of results to policy actors. Furthermore, our study will present the assessment of trans-European freight flows based on interesting future scenarios related to further congestion and the introduction of eco-taxes on transport in Europe.
Keywords: 330